Priority directions of provision of stable land use - Hun’ko, L. (Land Management, Cadastre and Land Monitoring, 2017)
The conditions of stable land use are highlighted in this article. The questionof the territory of agricultural enterprises is considered as well. The characteristicof the type of land use is given here. The recommendations are shown on the formationof ecologically safe types of land use. In the terms of new land relations is important toresolve the issue of land use regulation to with stand landscapes against adverse naturaland anthropogenic influences. The main instrument of the state, which aimsto provide an ecologically permissible and economically effective land use, land useis as an important component of land relations. Planning should include a systemof legal, technical, economic and environmental activities that will ensurethe preservation, restoration and rational use of land and other natural resourcesfor the benefit of the whole society.Keywords: land use, land management, stable development, landscape, soil erosion,protection of land.